Secretory carcinoma of the breast and its histopathological mimics: value of markers for differential diagnosis. Issue 4 (14th August 2013) - Osako, Tomo; Takeuchi, Kengo; Horii, Rie; Iwase, Takuji; Akiyama, Futoshi
<x xml:space="preserve">Abstract</x> Aims Secretory carcinoma (SC) is a rare histological type of breast cancer, and ETV6–NTRK3 gene fusion is highly specific to it. The differential diagnoses of SC include acinic cell carcinoma (ACCA) and cystic hypersecretory carcinoma (CHC), as well as invasive ductal carcinoma (IDC). For patients with these rare but distinctive histological subtypes, SC and its histopathological mimics should be differentiated from each other. However, differential markers have not yet been assessed systematically, and we aimed to identify and evaluate novel and existing markers. Methods and results We reviewed 19 cases diagnosed initially as SC using integrated diagnostic techniques, including morphology, immunohistochemistry and molecular pathology, and validated promising markers in 445 breast cancers. We reclassified 19 formerly diagnosed 'SCs' into nine SCs, three ACCAs, three CHCs, three IDCs and one microglandular adenosis. We confirmed that ETV6–NTRK3 gene rearrangement and amylase positivity are good diagnostic markers for SC and ACCA, respectively. Vacuolar staining for adipophilin, positivity for α‐lactalbumin and negativity for ETV6 rearrangement are diagnostic markers for CHC. Conclusions In this study, we propose a panel of four markers (ETV6 rearrangement, amylase, α‐lactalbumin and adipophilin) for distinguishing SC, ACCA, CHC and IDC. This simple but robust panel will serve pathologists well as a practical guide for reaching an appropriate diagnosis.